Successful combination of database search and snowballing for identification of primary studies in systematic literature studies - Wohlin, Claes; Kalinowski, Marcos; Romero Felizardo, Katia; Mendes, Emilia (Information and software technology, 2022)
A good search strategy is essential for a successful systematic literature study. Historically, database searches have been the norm, which was later complemented with snowball searches. Our conjecture is that we can perform even better searches if combining these two search approaches, referred to as a hybrid search strategy. Our main objective was to compare and evaluate a hybrid search strategy. Furthermore, we compared four alternative hybrid search strategies to assess whether we could identify more cost-efficient ways of searching for relevant primary studies. To compare and evaluate the hybrid search strategy, we replicated the search procedure in a systematic literature review (SLR) on industry–academia collaboration in software engineering. The SLR used a more “traditional” approach to searching for relevant articles for an SLR, while our replication was executed using a hybrid search strategy. In our evaluation, the hybrid search strategy was superior in identifying relevant primary studies. It identified 30% more primary studies and even more studies when focusing only on peer-reviewed articles. To embrace individual viewpoints when assessing research articles and minimise the risk of missing primary studies, we introduced two new concepts, wild cards and borderline articles, when performing systematic literature studies. The hybrid search strategy is a strong contender for being used when performing systematic literature studies. Furthermore, alternative hybrid search strategies may be viable if selected wisely in relation to the start set for snowballing. Finally, the two new concepts were judged as essential to cater for different individual judgements and to minimise the risk of excluding primary studies that ought to be included.